HISTORIS KAJIAN HAK AZASI MANUSIA DIDALAM HUKUM ISLAM - Gunawan, Syafri (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2020)
The aim of this research is that it is hoped that this research will contribute in terms of science and open up new opportunities for future researchers to examine more deeply the development of Islamic law in the field of human rights. The research method used is a qualitative methodology in the form of thematic research or library research. The results of this study, the researcher got several points or conclusions, including the source of the determination of human rights which is far different between Islamic studies that originate from the al-Qur'an and á¸¥adis and the West with philosophical guidelines without revelation guidance.